An Overview of Assistive Robotics and Technologies for Elderly Care - Christoforou, Eftychios G.; Panayides, Andreas S.; Avgousti, Sotiris; Masouras, Panicos; Pattichis, Constantinos S. (My University, 2019)
Population ageing is already having an impact on societies. This study briefly reviews associated technologies employed within the framework of elderly care, namely: robotic nursing, ambient assisted living and assistive robotics. Their current status is considered together with their potential and the associated implementation challenges.
Keywords: Assistive robotics; Elderly-care technologies; Nursing robots; Telerobotics; Human factors design